The importance of individual variation in the dynamics of animal collective movements. (26th March 2018) - del Mar Delgado, Maria; Miranda, Maria; Alvarez, Silvia J.; Gurarie, Eliezer; Fagan, William F.; Penteriani, Vincenzo; di Virgilio, Agustina; Morales, Juan Manuel
Abstract : Animal collective movements are a key example of a system that links two clearly defined levels of organization: the individual and the group. Most models investigating collective movements have generated coherent collective behaviours without the inclusion of individual variability. However, new individual-based models, together with emerging empirical information, emphasize that within-group heterogeneity may strongly influence collective movement behaviour. Here we (i) review the empirical evidence for individual variation in animal collective movements, (ii) explore how theoretical investigations have represented individual heterogeneity when modelling collective movements and (iii) present a model to show how within-group heterogeneity influences the collective properties of a group. Our review underscores the need to consider variability at the level of the individual to improve our understanding of how individual decision rules lead to emergent movement patterns, and also to yield better quantitative predictions of collective behaviour. This article is part of the theme issue 'Collective movement ecology'.